Application of HEC-RAS and Arc GIS for floodplain mapping in Segamat town, Malaysia - Noor Suraya, Romali; Zulkifli, Yusop; Ahmad Zuhdi, Ismail (GEOMATE International Society, 2018)
Nowadays, a risk-based flood mitigation concept has received more attention rather than the conventional flood control approach in reducing the impacts of flooding. With the intention to assist in the management of flood risk, flood modeling is useful in providing information on the flood extent and flood characteristics. This paper presents the application of HEC-RAS model to the development of floodplain maps for an urban area in Segamat town in Malaysia. The analysis used Interferometric Synthetic Aperture Radar (IFSAR) as the main modeling input data. Five distribution models, namely Generalized Pareto, Generalized Extreme Value, Log-Pearson 3, Log-Normal (3P) and Weibull (3P) were tested in flood frequency analysis to calculate extreme flows with different return periods. Using Kolmogorov-Smirnov (KS) test, the Generalized Pareto was found to be the best distribution for the Segamat River. The peak floods from frequency analysis for selected return periods were input into the HEC-RAS model to find the expected corresponding flood levels. Results obtained from HEC-RAS model were used in ArcGIS to prepare floodplain maps for different return periods. The results indicated that most of the inundated areas in the simulated 100 year return period were also affected by 2011 historical floods. For 100 years flood simulation, the inundated area was almost 5 times larger than the simulated 10 years’ flood.